Analisis Perbedaan Kejadian Ikutan Pasca Imunisasi (KIPI) Vaksin Coronavac Dosis Pertama dan Kedua pada Masyarakat Provinsi Jawa Tengah - Arifin Santoso; Indriyati Hadi Sulistyaningrum; Fildza Huwaina Fathnin; Atma Rulin Dewi Nugrahaeni; Abdur Rosyid; Syifa Audina Banin (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Adverse events following immunization (AEFI) for the coronavac vaccine are still widely found in Indonesia, especially in Central Java that happened in the first and second dose. The purpose of this study was to determine the difference between AEFI of the first and second dose of coronavac vaccine among recidents in Central Java. This cross-sectional study used a questionnaire with respondents from the recidents of central Java who carried out the first and second dose of coronavac. Statistical descriptive analysis, then an analysis of the differences of AEFI of the first and second dose of coronavac was carried out with dependent sample t-test. The results showed that the most common AEFI of coronavac were muscle pain at the first dose (11,2%) and the second dose (9,2%), followed by lethargy at the first dose (10,1%) and the second dose (8,3%), then pain accompanied by weakness in the arm injected at the first dose (8,8%) and the second dose (8,6%), and the swelling at the injection site at the first dose (7,5%) and the second dose (7,7%). There was no significant difference between AEFI that occurred after coronavac vaccination at the first and second dose as indicated by p value 0,320 (p 0,05).